2000
DOI: 10.1029/2000gl000016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ionospheric electron density fluctuations on satellite radar interferometry

Abstract: Abstract. Evidence is presented that auroral zone ionospheric disturbances can influence satellite radar interferometry (SRI) obtained with the RADARSAT, ERS and JERS-1 satellites. Fluctuations in ionospheric electron density can lead to an azimuth shift modulation in synthetic aperture radar (SAR) imagery, which can be detected using SRI. Measurements of azimuth shift in SRI can help to differentiate ionospheric from tropospheric propagation problems, and to understand better the impact of the ionosphere on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(125 citation statements)
references
References 9 publications
3
117
0
1
Order By: Relevance
“…Because of the timing of acquisitions (between 2000 and 0200 local time, when ionospheric scintillation is most intense), the location within about 20°of the magnetic equator (where these scintillations are most intense outside of the polar regions), and the fact that the distortions are only associated with single SAR images, we suspect that the distortions are of ionospheric origin [e.g., Xu et al, 2004]. The characteristics seem to vary across the regions, with streaks of decorrelation and phase perturbation in the central and southern Andes (similar to those seen in polar regions [e.g., Gray et al, 2000]) and only long spatial wavelength phase perturbations observed in the northern Andes. No ionospheric artifacts have been observed in Central America or the Caribbean arcs.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the timing of acquisitions (between 2000 and 0200 local time, when ionospheric scintillation is most intense), the location within about 20°of the magnetic equator (where these scintillations are most intense outside of the polar regions), and the fact that the distortions are only associated with single SAR images, we suspect that the distortions are of ionospheric origin [e.g., Xu et al, 2004]. The characteristics seem to vary across the regions, with streaks of decorrelation and phase perturbation in the central and southern Andes (similar to those seen in polar regions [e.g., Gray et al, 2000]) and only long spatial wavelength phase perturbations observed in the northern Andes. No ionospheric artifacts have been observed in Central America or the Caribbean arcs.…”
Section: Discussionmentioning
confidence: 99%
“…[10] In the CVZ, both descending and ascending interferograms regularly show correlated noise that varies with atmospheric water vapor concentrations [Fournier et al, 2011]. Ascending tracks, which are acquired at approximately 10 P.M. local time in the CVZ, can have additional large ionospheric signals that are related to variability in electron density [e.g., Gray et al, 2000;Xu et al, 2004]. Ionospheric signals are easily identified as SW-NE trending, high amplitude streaks that are roughly parallel to the Earth's magnetic field at this latitude [Loveless et al, 2010;Fournier et al, 2010].…”
Section: Sources Of Noisementioning
confidence: 99%
“…Ionospheric disturbances cause phase gradient resulting in azimuth shifts, called "azimuth streaks" [10]. Large scale variations of the total electron content of the ionosphere also yield slight range shifts between the SAR images [11].…”
Section: Calibrationmentioning
confidence: 99%